Preserving freshness: innovations for fresh-eating fruit distribution and damage prevention – A review - Yu, Jincheng; Wang, Minggang; Li, Zhiguo; Tchuenbou-Magaia, Fideline; Wani, Ali Abas; Zhu, Pengfei; Fadiji, Tobi; Liu, Yande (Elsevier, 2024)
The preservation of fresh-eating fruit within the supply chain is of paramount for maintaining freshness and minimizing resource waste. This article elucidates a comprehensive and integrated approach to fruit loss prevention and preservation techniques which collectively can substantially prolong the shelf life of fresh-eating fruits across various supply chain contexts. Here we show that the proposed solution emphasizes the development of real-time damage monitoring systems, innovative sensors for fruit freshness detection, and predictive methods for quality degradation and estimating shelf life. Additionally, we advocate for fundamental research to support the creation of smart, lightweight, sustainable, shockproof packaging systems. These packaging systems aim to utilize recyclable and biodegradable materials, contributing to environmental sustainability. In conclusion, this study establishes a scientific foundation for innovative solutions in the preservation and damage avoidance of fresh-eating fruits within the supply chain. By considering diverse factors and proposing a holistic approach, we anticipate substantial advancements in preserving the freshness of fruits.
Keywords: Fresh fruit; Packaging; Mechanical damage; Fruit quality; Sustainability